2011
DOI: 10.1186/1476-4598-10-136
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid pathway activity in wilms tumors and characterization of biological responses in vitro

Abstract: BackgroundWilms tumor (WT) is one of the most common malignancies in childhood. With current therapy protocols up to 90% of patients can be cured, but there is still a need to improve therapy for patients with aggressive WT and to reduce treatment intensity where possible. Prior data suggested a deregulation of the retinoic acid (RA) signaling pathway in high-risk WT, but its mode of action remained unclear.ResultsThe association of retinoid signaling and clinical parameters could be validated in a large indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…The pro-apoptotic effect of fenretinide has been shown in various cancer cell lines including HeLa and breast cancer cell lines, whereas ATRA has shown no growth inhibition effect in these cell lines (26). Fenretinide also induces apoptosis/necrosis in primary Wilm’s tumor cell, but ATRA promotes cell growth (27). The apoptosis effect of fenretinide is cancer cell specific, it does not induce apoptosis in normal hepatocyte (15).…”
Section: Discussionmentioning
confidence: 99%
“…The pro-apoptotic effect of fenretinide has been shown in various cancer cell lines including HeLa and breast cancer cell lines, whereas ATRA has shown no growth inhibition effect in these cell lines (26). Fenretinide also induces apoptosis/necrosis in primary Wilm’s tumor cell, but ATRA promotes cell growth (27). The apoptosis effect of fenretinide is cancer cell specific, it does not induce apoptosis in normal hepatocyte (15).…”
Section: Discussionmentioning
confidence: 99%
“…Lapatinib-resistant cell lines (rBT474, rSKBR3, rAu565, and rSUM190) were generated and continuously maintained in 1 μ M lapatinib, as previously described [17,18]. The 4G10 anti-phosphotyrosine (p-tyr) antibody was purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the methods used for SDS-PAGE and Western blot analysis have been previously described [17,18,26]. In brief, membranes were incubated with primary antibodies, washed several times in PBS, and then incubated with a fluorescence-conjugated secondary antibody at a 1:10,000 dilution with 5% try milk in PBS for 60 minutes, protected from light.…”
Section: Methodsmentioning
confidence: 99%
“…UAB30 has minimal toxicity compared to other retinoids [7, 911], and has recently been found to be effective in decreasing xenograft tumor growth in neuroblastoma [12]. Investigators have demonstrated the effectiveness of retinoids against adult liver [13] and kidney tumors [14]. These data in neuroblastoma [12], and the prior results with retinoids in adult renal and hepatic malignancies [13, 14], led us to believe that UAB30 may have an effect upon tumorigenicity in rare pediatric renal and hepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have demonstrated the effectiveness of retinoids against adult liver [13] and kidney tumors [14]. These data in neuroblastoma [12], and the prior results with retinoids in adult renal and hepatic malignancies [13, 14], led us to believe that UAB30 may have an effect upon tumorigenicity in rare pediatric renal and hepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%